Application of Memorizing Short Letters at MTs Negeri 12 Jatibarang, Indramayu Regency - Ibnu Rusydi; Didik Himmawan; Siti Muamaliyah Hairunnisa (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
This research aims to describe the importance of implementing short letter reading at MTs Negeri 12 Jatibarang which is carried out in daily activities. The Al-Qur'an is a holy book that was revealed to the Prophet Muhammad SAW as guidance, lessons and life guidelines for Muslims. Memorizers of the Koran are people who have been chosen by Allah SWT throughout the history of human life to maintain the purity of the Koran. MTs 12 Jatibarang has a superior program, namely the Al-Qur'an tahfidz class. This research uses a qualitative descriptive approach, the research object is the learning method for applying short letters. Meanwhile, the subjects of this research were the school principal, Ustadz supervisor, and students who were undergoing the memorization process. The aim of this research is to improve students' ability to memorize the Koran through short letters first. Based on the research results, it can be concluded that the implementation of short letters at MTs Jatibarang is effective in increasing students' memorization and religiosity. Even though there are obstacles in its implementation, this research also provides solutions for teachers and students in implementing short letters.